GAYA BAHASA SATIRE PADA IMPERSONATE KONTEN KREATOR TIKTOK KAJIAN STUDI LITERATURE - Trikandi, Sonya; Saputro, Pramisdi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to describe the language style of deep satire impersonate DRL account content by Doksun content period “DRL Samperi Doksun”. The research method uses a qualitative research method, a descriptive approach to sentences that contain a satirical language style. The data source in the research is satirical language style impersonate Doksun content period “DRL Samperi Doksun”. The data in the research is in the form of speech fragments containing a satirical language style delivered by Doksun to satirize DRL. Data collection techniques use listening and note-taking techniques. The data analysis technique uses content analysis techniques, the researcher concludes systematically. The results of research on satirical language styles are available impersonate DRL by the Doksun account has satirical language styles, namely Horation satire and juvenalian satire. Horatian satire on Doksun content in the form of satire to criticize DRL which always has an elite style and gives a humorous impression of everything that DRL does but is not yet known to the public. Satire Horation takes the form of direct satire against DRL for engineering content that causes an imbalance between each other.